2003
DOI: 10.1007/s11745-003-1129-2
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with CLA: Isomer incorporation into serum lipids and effect on body fat of women

Abstract: Animal studies have suggested that CLA, a natural component of meat and dairy products, may confer beneficial effects on health. However, human studies using supplementation with CLA have produced contradictory results. The aim of the present study was to further investigate the effect of CLA supplementation on human body fat, serum leptin, and serum lipids, as well as the incorporation of CLA isomers into serum lipids classes. Sixteen young healthy nonobese sedentary women received 2.1 g of CLA (divided equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
69
5
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 21 publications
11
69
5
11
Order By: Relevance
“…Smedman and Vessby (2001) showed that intake of 4.2 g CLA/day for 12 weeks did not affect serum lipid or lipoprotein concentrations. No effect on serum TG, TC, and HDL-C was again reported by Petridou et al (2003) when they studied the effect of supplementation of 2.1 g CLA/day for 45 days in non-obese young sedentary women.…”
Section: Cla and Lipidsmentioning
confidence: 82%
“…Smedman and Vessby (2001) showed that intake of 4.2 g CLA/day for 12 weeks did not affect serum lipid or lipoprotein concentrations. No effect on serum TG, TC, and HDL-C was again reported by Petridou et al (2003) when they studied the effect of supplementation of 2.1 g CLA/day for 45 days in non-obese young sedentary women.…”
Section: Cla and Lipidsmentioning
confidence: 82%
“…A 6.4 g day 21 MI-CLA doses for 12 weeks produced a modest increase in lean mass (0.6 kg) but significant decrease in serum HDL-cholesterol, sodium, hemoglobin, and hematocrit, and significant increases in serum alkaline phosphatase, C-reactive protein, and K-6, and white blood cells. Plasma triacylglycerides (TAG) did not significantly change or decrease compared to placebo in some studies with MI-CLA supplementation 33,59,62,63 . Nevertheless, in another study mean plasma TAG concentration was higher during supplementation with a mixture 85% trans-10,cis-12 CLA than with another mixture 80% cis-9,trans-11 CLA 24 .…”
Section: Metabolic Effects Of Conjugated Linoleic Acidmentioning
confidence: 99%
“…(2003) (16) Sixteen females, healthy sedentary normal-weight and overweight (19) Sixty males and females, healthy overweight…”
Section: Conjugated Linoleic Acid Supplementation and Ldl Cholesterolmentioning
confidence: 99%